Physicochemical characterization and thermal behavior of biodiesel and biodiesel diesel blends derived from crude Moringa peregrina seed oil - Salaheldeen, M.; Aroua, Mohamed Kheireddine; Mariod, A.A.; Cheng, Sit Foon; Abdelrahman, M.A.; Atabani, A.E. (Elsevier, 2015)
Moringaceae is a monogeneric family with a single genus i.e. Moringa. This family includes 13 species. All these species are known as medicinal, nutritional and water purification agents. This study reports, for the first time, on characterization of the biodiesel derived from crude Moringa peregrina seed oil and its blends with diesel. The crude oil was converted to biodiesel by the transesterification reaction, catalyzed by potassium hydroxide. High ester content (97.79) was obtained. M. peregrina biodiesel exhibited high oxidative stability (24.48 h). Moreover, the major fuel properties of M. peregrina biodiesel conformed to the ASTM D6751 standards. However, kinematic viscosity (4.6758 mm(2)/s), density (876.2 kg/m(3)) and flash point (156.5 degrees C) were found higher than that of diesel fuel. In addition, the calorific value of M. peregrina biodiesel (40.119 MJ/kg) was lower than the diesel fuel. The fuel properties of M. peregrina biodiesel were enhanced significantly by blending with diesel fuel. In conclusion, M. peregrina is a suitable feedstock for sustainable production of biodiesel only blended up to 20 with diesel fuel, considering the edibility of all other parts of this tree. (C) 2015 Elsevier Ltd. All rights reserved.